Abnormal 30S Ribosomal Subunits Determined by an Ochre Suppressor Mutation in Escherichia coli - Reid, Parlane (1969)
The results demonstrate that an ochre suppressor mutant of Escherichia coli K-12 produces abnormal 30S ribosomes. The production of these abnormal 30S ribosomes is probably a secondary consequence of the suppressor mutation.